X - Y = -1
3x - 2y = 0
Respuestas a la pregunta
Contestado por
7
Respuesta:
X= 2
Y=3
Explicación paso a paso:
X - Y = -1
3x - 2y = 0
(-2)X - (-2)Y = -1(-2)
3x - 2y = 0
-2x +2y = 2
3x - 2y = 0
3x - 2x = 0+2
X = 2
Ahora escogemos la primera ecuación y reemplazamos X
X - y = - 1
2 - y = - 1
2 +1 = y
3 = y
Comprobación
3(x) - 2(y)=0
3(2) - 2(3)=0
6 - 6 =0
Otras preguntas
Física,
hace 5 meses
Historia,
hace 5 meses
Inglés,
hace 5 meses
Castellano,
hace 10 meses
Ciencias Sociales,
hace 10 meses
Filosofía,
hace 1 año
Matemáticas,
hace 1 año